“Iron-Deficiency Anemia In Children And Adolescents In Uzbekistan” (Eurasian Medical Research Periodical, 2026)
This paper examines the issue of iron-deficiency anemia in children and adolescents, a condition that remains one of the most prevalent pathologies in our country today. Particular attention is focused on the current situation in Uzbekistan, where, despite ongoing preventive measures, the rate of iron deficiency remains notably high. The study analyzes the primary causes underlying the development of this condition, highlighting factors such as an unbalanced diet, increased physiological requirements during periods of growth, and the impact of chronic diseases and socioeconomic factors. Special consideration is given to the specific clinical characteristics of iron-deficiency anemia in adolescents, particularly in girls. Furthermore, the article briefly presents current data regarding the prevalence of anemia—both within Uzbekistan and globally—thereby providing a context for assessing the true scale of the problem. The paper underscores the impact of iron deficiency on the physical and cognitive development of children, as well as its role in diminishing their overall quality of life. The objective of this study is to investigate the prevalence, etiology, and risk factors associated with iron-deficiency anemia in children and adolescents, and to establish its significance as a critical public health concern.